Mechanism of anticlastogenicity of Agaricus blazei Murill mushroom organic extracts in wild type CHO (K-1) and repair deficient (xrs5) cells by chromosome aberration and sister chromatid exchange assays - Luiz, R. C.; Jordao, B. Q.; da Eira, A. F.; Ribeiro, L. R.; Mantovani, M. S. (Elsevier B.V., 2003)
Agaricus blazei Murill is a medicinal mushroom native to Brazil. The present work assessed the clastogenic and anticlastogenic potential of organic extracts (ethanol and chloroform/methanol) from the lineage AB97/11 in chinese hamster CHO-K-1 (wild type) and CHO-xrs5 (repair deficient) cells using the chromosome aberration (CA) and sister chromatid exchange (SCE) assays. In these experimental conditions were observed: (a) anticlastogenic effect at concentrations of 0.06 and 0.09% of the EtOH extract and at the 0.03 and 0.06% concentrations of the C/MetOH extract in CHO-K-1; (b) absence of protector effect on CHO-xrs5 cells; and (c) absence of protector effect in the SCE assay. These results indicate that organic extracts of A. blazei lineage AB97/11 present bio-antimutagenic type protective activity. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Agaricus blazei Murril; chromosome aberration assay; sister chromatid exchange assay; CHO cells; methyl methanesulphonate